Africa Energy Poverty : G8 Energy Ministers Meeting 2009 - World Bank (Washington, DC, 2013)
Worldwide, about 1.6 billion people lack access to electricity services. There are also large populations without access in the poorer countries of Asia and Latin America, as well as in the rural and peri-urban areas of middle income countries. However large-scale electrification programs that is currently underway in middle income countries and the poor countries of Asia will increase household electricity access more rapidly than in sub-Saharan Africa. Africa has the lowest electrification rate of all the regions at 26 percent of households, meaning that as many as 547 million people are without access to electricity. On current trends less than half of African countries will reach universal access to electricity even by 2050. Without access to electricity services, the poor are deprived of opportunities to improve their living standards and the delivery of health and education services is compromised when electricity is not available in clinics, in schools and in the households of students and teachers. The total financing needs for Africa to resolve the power supply crisis are of the order of approximately US$40 billion per annum or 6.4 percent of region's Gross Domestic Product (GDP). In response to the power crisis, donors have increased their support to the power sector, though more is needed. From the mid-1990s to the mid-2000s, donor assistance for the African power sector averaged no more than US$500 million per year. The private sector will be key to energy access expansion. For example, private sector expertise will be needed to develop the large complex generation and transmission projects (especially cross-border projects) that are necessary and for which a project finance approach will be often the most appropriate. The current global credit crisis poses additional challenges to mobilizing financing for energy infrastructure and especially for projects with perceived higher risk or higher costs. Nevertheless, governments can still access finance in the private markets for sound investments.